AGOA Expiry: Nonrenewal Welfare, Macroeconomic and Trade Effects - Mhonyera, Gabriel (Theoretical and Practical Research in Economic Fields; Vol 16 No 4 (2025): TPREF Special Issue, Volume XVI, Issue 4(36), Winter 2025, 2025)
The expiry of the African Growth and Opportunity Act (AGOA) in 2025 has raised uncertainty about the future of United States–Sub-Saharan Africa trade relations. This study employs the Global Trade Analysis Project (GTAP) Computable General Equilibrium (CGE) model to assess the potential trade, welfare, and macroeconomic impacts of AGOA’s non-renewal under two scenarios: the reversion of US tariffs to Most Favoured Nation (MFN) levels and the imposition of a uniform 10% reciprocal tariff. Results (see Scenario 2) indicate that AGOA countries could experience welfare losses of up to US$1.78 billion and GDP contractions of 0.52%, accompanied by significant declines in exports of textiles, mining, and manufacturing. The United States (US) would also face moderate welfare losses, while China and the EU would gain from trade diversion. The findings highlight the urgent need for Sub-Saharan African countries to diversify trade partnerships and negotiate new frameworks to mitigate adverse post-AGOA outcomes.